Oscar and the amazing gravity repellent - Peterson, Tina L; Bonet, Xavier (North Mankato, Minnesota Capstone Young Readers, a Capstone imprint, 2016)
Oscar Schmidt is a klutz and gravity is his nemesis - it pulls him down, trips him up, and helps the neighborhood bullies make his life all-around awful. But when Oscar finds an abandoned train caboose one day after school, everything changes. Inside, he discovers a magical potion: Dr. Oopsie's Amazing Gravity Repellent. Along with his best friend, Asha, Oscar learns what happens when he defies the laws of nature
A gift from book Africa
English stories
1 2 13 15
NEW_ZTN_GN
Keywords: Gravity -- Juvenile fiction; Self-confidence -- Juvenile fiction